Revisiting the gender revolution: Time on paid work, domestic work, and total work in East Asian and Western Societies 1985–2016 - Kan, MY; Zhou, M; Kolpashnikova, K; Hertog, E; Yoda, S; Jun, J (SAGE Publications, 2022)
We analyze time use data of four East Asian societies and 12 Western countries between 1985 and 2016 to investigate the gender revolution in paid work, domestic work, and total work. The closing of gender gaps in paid work, domestic work, and total work time has stalled in the most recent decade in several countries. The magnitude of the gender gaps, cultural contexts, and welfare policies plays a key role in determining whether the gender revolution in the division of labor will stall or continue. Women undertake more total work than men across all societies: The gender gap ranges from 30 minutes to 2 hours a day. Our findings suggest that cultural norms interact with institutional contexts to affect the patterns of gender convergence in time use, and gender equality might settle at differing levels of egalitarianism across countries.